Philosophy and Transformative Learning: Lessons in Natural Resource Management from Cordillera Communities - Mendoza, Julius D. (Archīum Ateneo, 2024)
In this paper, the objects of philosophical reflection are the important lessons learned from a participatory action research program conducted by the Cordillera Studies Center of UP Baguio in Sagada, Mountain Province, in Northern Luzon, Philippines, which ran from March 1997 to February 2001. This research program used the Community Based Natural Resource Management (CBNRM) approach. Concepts of philosophy are made to re-describe “second order” concepts of theory, as well as “first order” concepts of community-based natural resource management research, planning, testing, implementation, and monitoring. Concepts used in the context of field work are given philosophical re-descriptions in the form of the ontology of societal totality and nature, ethical thinking applied to land rights and to collective action of marginalized groups, and in the form of epistemological assertions concerning the interaction of indigenous knowledge and the conduct of scientific research itself on a community-based natural resource management.